The effects of using cognitive discourse functions to instruct 4th-year children on report writing in a CLIL science class - Roca de Larios, Julio; Coyle, Yvette; García, Vanessa (Studies in Second Language Learning and Teaching, 2022)
The present study analyzed how a group of young Spanish-speaking English as a foreign language (EFL) learners in a content and language integrated learning (CLIL) science class responded to an instructional unit integrating attention to functional language and an inquiry-oriented approach to science. Working in cooperation with the researchers, a year 4 primary school teacher implemented a teaching sequence on levers with 48 9-10-year-olds over three weeks. The sequence, which was intended to raise the children’s awareness of the demands involved in understanding (content goals) and expressing as written reports (rhetorical goals) how levers work, scaffolded their activity from item-based writing to the production of full texts. On completing the unit, each child independently wrote a report on levers, all of which were analyzed from the perspective of cognitive discourse functions and ideational meaning. The results of these analyses are discussed in terms of their significance for CLIL writing with young learners.